EAAT5 Glutamate Transporter-Mediated Inhibition in the Vertebrate Retina - Lukasiewcz, Peter D.; Bligard, Gregory W.; DeBrecht, James D. (Frontiers in Cellular Neuroscience, 2021)
Glutamate transporters typically remove glutamate from the synaptic cleft. In addition, all glutamate transporters have a chloride channel, which is opened upon glutamate binding to the transporter. There are five types of glutamate transporter (EAATS1-5, excitatory amino acid transporters), which have distinct chloride conductances. Some EAATS that have low chloride conductances, remove glutamate from the synaptic cleft most effectively (e.g., EAAT1). By contrast, EAATs that have high chloride conductances, remove glutamate less effectively (e.g., EAAT5). We have studied EAAT5 in the retina. In the retina, light activates a chloride current, mediated by the glutamate activation of EAAT5. EAAT5 is not a significant contributor to lateral inhibition in the retina. Instead, it is the main source of autoinhibition to rod bipolar cells (RBCs). EAAT5-mediated inhibition has a substantial effect on synaptic transmission from RBCs to downstream retinal neurons.